A flexible and low-cost open-source IPMC mezzanine for ATCA boards based on OpenIPMC. (1st March 2022) - Calligaris, L.; Cascadan, A.; Ardila-Perez, L.E.; Pesaresi, M.; Fedi, G.; Peck, A.; Gastler, D.
Abstract: This work presents the development of an Intelligent Platform Management Controller mezzanine in a Mini DIMM form factor for use in electronic boards compliant to the PICMG Advanced Telecommunication Computing Architecture (ATCA) standard. The module is based on an STMicroelectronics STM32H745 microcontroller running the OpenIPMC open-source software. The mezzanine has been successfully tested on a variety of ATCA boards being proposed for the upgrade of the experiments at the HL-LHC, with its design and firmware being distributed under open-source hardware license.